The fragile bonds of love: Examining partner affirmation and commitment uncertainty as predictors of infidelity among married individuals in Malaysia - Chang, Shan Mei; Tay, Shi Swen; Wong, Ming Jie (2025)
Divorce cases attributed to infidelity have increased significantly, raising a serious concern about the stability of marriages in Malaysia. Infidelity in marriage not only causes severe psychological pain and trauma to spouses, but also negatively impacts other family members, making it a broader social issue. This study examined the predictive role of partner affirmation on infidelity among married individuals in Malaysia and investigated the mediating role of commitment uncertainty. A quantitative, cross-sectional research design was employed in this study. Data were collected through an online Qualtrics survey using purposive sampling. A total of 146 married Malaysians (Mage = 36.47, SDage = 10.07, Females = 69.2%, Chinese = 50%) participated. Sexual and Emotional Infidelity Scale (SEI), Partner Affirmation Scale (PAS), and Commitment Uncertainty Short Scale (CUSS) were utilised to measure the variables of the study. The results indicated that partner affirmation significantly and negatively predicted infidelity among married individuals in Malaysia. Besides, commitment uncertainty significantly mediated the relationship between partner affirmation and infidelity. These findings provide important insights for both married couples and practitioners by highlighting the importance of partner affirmation and commitment certainty in reducing the likelihood of infidelity. They also fill a knowledge gap in Malaysia by highlighting partner affirmation predicts infidelity both directly and indirectly through commitment uncertainty. Meanwhile, the findings extend the Investment Model by incorporating partner affirmation and commitment uncertainty to capture broader aspects of infidelity.